Model Hospital Company Image Pride-Based Organizational Behavior - Dodi Wijaya; Iis Rahmawati; Nurfika Asmaningrum; Kholid Rosyidi Muhammad Nur (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Introduction: The globalization era makes the hospital service industry competition even higher, which requires hospital management to develop strategies to face competition. The efforts made by the hospital in the face of this competition by encouraging staff to engage in Organization Citizenship Behavior (OCB). Nurses as health workers who provide care to patients play an important role in being involved in OCB to build a positive image of the hospital. More and more staff involved in OCB can improve service efficiency, and patient satisfaction, and provide positive value to Hospital's Corporate Image (HCI). Objective: This study aims to compile an OCB-based HCI model. Materials and Methods: This study used an analytical observational design with a cross-sectional approach. The study sample involved 260 patients spread across five plantation hospitals that are members of the Indonesia Healthcare Corporation in The Eastern Salient of Java, East Java Province, Indonesia. Variables consist of 7 latent variables and 25 indicators.  Inferential analysis using SEM PLS. Results: The results showed that (1) the determinants of OCB were influenced by employee factors, company factors, and customer factors, (2) employee factors had the most influence on OCB which had a positive impact on HCI, (3) OCB was a mediating variable between employee and HCI factors, (4) OCB had a strong influence on HCI. Conclusion: The OCB-based HCI model is a model that is influenced by employee factors through good nurse interpersonal communication to improve nurses' OCB behavior through tolerance behavior (sportsmanship) to create a positive hospital image. Plantation hospitals in Indonesia that are members of the Indonesia Healthcare Corporation need to start thinking about efforts to improve employee factors through the competence of interpersonal communication of nurses in providing services to patients.